Importance of self‐weighing to avoid post‐cessation weight gain: A secondary analysis of the fit and quit randomized trial - Mackenzi Oswald; Kathryn M. Ross; Ning Sun; Wupeng Yin; Stephanie J. Garcia; Zoran Bursac; Rebecca A. Krukowski (Wiley, 2023)
Abstract Background Smoking cessation is associated with weight gain, and the risk of weight gain is a common deterrent to quitting smoking. Thus, the identification of strategies for reducing post‐smoking cessation weight gain is critical. Objective Conduct secondary analysis of data from the Fit & Quit trial to determine if greater frequency of self‐weighing is associated with less weight gain in the context of smoking cessation. Methods Participants (N = 305) were randomized to one of three 2‐month weight interventions (i.e., Stability, Loss, Bibliotherapy), followed by a smoking cessation intervention. Stability and Loss conditions received different types of self‐weighing feedback. All participants received e‐scales at baseline, to capture daily self‐weighing data over 12 months. General linear models were applied to test the main objective. Results Frequency of self‐weighing was (mean ± SD) 2.67 ± 1.84 days/week. The Stability condition had significantly higher self‐weighing frequency (3.18 ± 1.72 days/week) compared to the Loss (2.51 ± 1.99 days/week) and the Bibliotherapy conditions (2.22 ± 1.63 days/week). Adjusting for baseline weight and treatment condition, self‐weighing 3-4 days/week was associated with weight stability (−0.77 kg, 95% CI: −2.2946, 0.7474, p = 0.3175), and self‐weighing 5 or more days/week was associated with 2.26 kg weight loss (95% CI: −3.9249, −0.5953, p = 0.0080). Conclusions Self‐weighing may serve as a useful tool for weight gain prevention after smoking cessation. Feedback received about self‐weighing behaviors and weight trajectory (similar to the feedback Stability participants received) might enhance adherence.